The orthodontic extraction of permanent molars: a literature review - Chua Emilia S.L; Felicita A. Sumathi (Sciendo, 2015)
The most common cause of dental crowding is the presence of an arch-length - tooth-size discrepancy. Conventional methods of gaining space in orthodontics involve the extraction of teeth, often premolars. However, there are a number of clinical situations in which the extraction of permanent molars might be considered. This paper highlights the indications, advantages, disadvantages and timing of the extraction of the first, second and third permanent molars in the treatment of a crowded malocclusion.